Implementación de una aplicación web de bolsa de empleo para la Junta Provincial de Defensa del Artesano en la ciudad de Guaranda, año 2023 - Caluña Mullo, Delia Cristina (2023)
The technological project allows the automation in the process of contracting artisans and potentiation of the artisan labor offer, with the implementation of the web application of employment exchange for the Provincial Board of Defense of the Artisan, the lack of diffusion of the services that offered by artisans and is increased with a wide variety of options when making a contract in an artisan category, all this is the result of correctly applying software engineering since it is in charge of the aspects of software production from the best of the product until its maintenance. To carry out this program, an agile development methodology was changed, Extreme Programming (XP) because it ensures great control over projects and a more effective implementation since it is based on communication, code reuse and feedback. It began with the analysis of the current situation of artisans and employers through surveys, which helped in data collection and determination of requirements. Once the requirements were determined, the software modeling was carried out using the Unified Modeling Language (UML) in order to define the user interfaces. For the design of the logical structure of the project, the Model View Controller (MVC) architectural pattern was taken as it is preferred by most programmers. Finally, the web application was subjected to a test to verify that the software fulfills its function. Keywords: labor potentiation, contracting, Extreme Programming, Unified Modeling Language, web application.